Energy and Environment b Proceedings of the 2014 International Conference on Energy and Environment (ICEE 2014), Beijing, China, 26-27 June 2014 - Zheng, Dawei (IRAICS proceedings series, 2014)
The 2014 International Conference on Energy and Environment (ICEE 2014) was held June 26-27 in Beijing, China. The objective of ICEE 2014 was to provide a platform for researchers, engineers, academics as well as industry professionals from all over the world to present their research results and development activities in Energy and Environment research. The program consisted of invited sessions and technical workshops and discussions with eminent speakers, and contributions to this proceedings volume cover a wide range of topics in Energy and Environment studies